Godsbegrippe en die funksie van metafore in die rousmartproses 1 - Smith, W. (Hervormde teologiese studies, 2000)
Grief, metaphors and images of God. This article atempts to give new meaning to the discussion of "grief," "metaphors's" and "images of God" in such a way that new meaning of life within grief becomes a spiritual way of living, a life coram Deo. It is argued that the task of the pastor should be to communicate the different images of God on a conscious level so that the person undergoing counselling could develop the ability to evaluate his or her own images of God, which had been subconscious, on to a conscious level, in order to live the hope in Jesus Christ as an eschatological and pneumatical happening.